5 - How Women in Higher Education Negotiate Work and Home: A Study of Selected Women at a University in South Africa - Deevia Bhana,; Venitha Pillay, (Journal of Higher Education in Africa, 2012)
The Council for Higher Education notes the lack of women doing research in South African universities. Focusing on the experiences of South African women academics, this article highlights the ways in which inequitable gender relations fuel women’s marginalized position in higher education. The findings reported here include the gendered dimensions of negotiating home and work, pointing both to obstacles that limit women’s agency and to prospects for hope by elucidating new possibilities for the development of women’s agency. Being women in higher education and mothers is at the same time is regulated by restrictive understandings of gender. But women are not simply victims of this discourse. Hence, greater care must be taken in understanding women’s gendered roles that inhibit their greater participation in research. Transforming gender relations and working towards equity are, therefore, crucial to women’s success.